Correlation between obstructive sleep apnea and central retinal vein occlusion - Wang, Yan-Hui (Int J Ophthalmol, 2019)
To investigate the possible correlation between obstructive sleep apnea (OSA) and central retinal vein occlusion (CRVO). Thirty consecutive patients with a recent (<3mo) CRVO and an age- and sex-matched group of 30 control subjects were recruited. All subjects underwent full-night polysomnography to measure apnea-hypopnea index (AHI) and oxygen desaturation index (ODI). The average AHI and ODI were significantly higher in CRVO patients (AHI: 13.86±8.63, ODI: 9.21±4.47) than in control subjects (AHI: 8.51±6.36, ODI: 5.87±3.18; P=0.008 and 0.001 respectively). Additionally, the AHI was positively correlated with body mass index (BMI; r=0.476, P=0.017) and ODI (r=0.921, P<0.01) in both CRVO and control subjects. According to AHI scores, twenty-two (73.33%) CRVO patients had OSA and 12 (40.00%) control subjects had OSA, a difference that was statistically significant (P=0.019). OSA may be a risk factor for or a trigger of CRVO development.